The effects of full‐stream and partial high‐pressure homogenisation on the properties of milk emulsion. (15th September 2022) - Kiełczewska, Katarzyna; Brożek, Oskar; Rudkowska, Paulina; Garczewska‐Murzyn, Anna; Smoczyński, Michał
Summary: The study evaluated the effects of full‐stream and partial high‐pressure homogenisation (HPH) on the properties of milk with 3.5% fat content. During full‐stream HPH, the size of particles decreased with an increase in temperature. Fat globules were smaller in milk treated by full‐stream than partial HPH at 60°C. Creaming was not observed in milk subjected to full‐stream HPH. In milk treated by partial HPH, the phase separation rate during ≤48 h of storage increased in samples processed at 60°C, 40°C and 20°C. Despite high top layer volume in milk that was HPH‐treated at a temperature of ≥40°C, its fat content was lower than in milk homogenised at 20°C. The total difference in colour was approximately 1.5–2.0‐fold higher in full‐stream homogenised milk. Partial HPH can be applied in dairy products requiring milk fat dispersion with minimal changes in the components of the colloidal and soluble phases. Abstract : This study evaluates the effects of full‐stream and partial high‐pressure homogenisation on the properties of milk with 3.5% fat content. Partial homogenisation has economic advantages and can be applied in dairy products requiring milk fat dispersion with minimal changes in the components of the colloidal and soluble phases.